FIGURATIVE LANGUAGE USED IN JENNIE FROM BLACKPINK INTERVIEW WITH ELLE MAGAZINE - Miftahul Hasanah; Yuliyanto Sabat; Sulistyaningsih Sulistyaningsih (IKIP Siliwangi, 2024)
Jennie, a popular star with millions of fans, used fictional language in an exclusive interview with ELLE magazine. She used figurative language to attract attention, bring personal stories to life, and create profound impressions. Jennie's unique speaking style blended fictional meaning and authentic self-expression, solidifying her position as a modern pop icon. This study used qualitative-descriptive research to accurately describe the object and explain the data in a systematic and thorough manner. The data for this study came from Jennie from Blackpink's YouTube channel, Elle. The documentary technique was used to collect data, which was applied to written or visual materials in order to identify certain qualities of the material, such as textbooks, speeches, ads, or any of these. Based on data taken by researchers, they found that there were 25 sentences, 5 of which contained figurative language and 20 of which did not contain it. In 5 sentences containing figurative language, there were 1 sentences using hyperbole, 3 with metaphors and 1 with repetitions. Jennie effectively used metaphors, personification, idioms, and repetitions to convey her emotions and reality in an interview, creating captivating images and a concise message.